Molecular control over Ag/p-Si diode by organic layer - Aydin, M. E.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2007)
Electrical transport properties of Ag metal-fluorescein sodium salt (FSS) organic layer-silicon junction have been investigated. The current-voltage (I-V) characteristics of the diode show rectifying behavior consistent with a potential barrier formed at the interface. The diode indicates a non-ideal I-V behavior with an ideality factor higher than unity. The ideality factor of the Ag/FSS/p-Si diode decreases with increasing temperature and the barrier height increases with increasing temperature. The barrier height (phi(b) = 0.98 eV) obtained from the capacitance-voltage (C-V) curve is higher than barrier height (phi(b) = 0.72 eV) derived from the I-V measurements. The barrier height of the Ag/FSS/p-Si Schottky diode at the room temperature is significantly larger than that of the Ag/p-Si Schottky diode. It is evaluated that the FSS organic layer controls electrical charge transport properties of Ag/p-Si diode by excluding effects of the SiO2 residual oxides on the hybrid diode. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: semiconductors; organic compounds; electrical properties